Veloсity dispersion of dust particles confined in a sheath - Zasenko, V.I. (Вопросы атомной науки и техники, 2019)
Velocity distribution of dust particles localized in a plasma sheath near an electrode was found in a number of experiments. Velocity dispersion indicated that the kinetic temperature of dust grains significantly exceeds the temperature of plasma environment. Consequently, the question arose about the stochastic mechanisms of anomalous heating of grains. We propose the model in which the kinetic energy is due to the significant potential energy that grains have at the moment of their release from the crystalline structure on melting. Stochastic processes only modify the regular motion of dust grains, forming a velocity distribution similar to а Gaussian. У ряді експериментів визначався швидкісний розподіл порошинок, локалізованих в приповерхневому шарі плазми поблизу електрода. Дисперсія швидкості вказувала на те, що кінетична температура порошинок значно перевищує температуру плазмового оточення. Відповідно постало питання про стохастичні механізми аномального нагрівання порошинок. Запропоновано модель, в якій кінетична енергія порошинок обумовлена значною потенціальною енергією, яку частинки мають у момент вивільнення з кристалічної структури при плавленні. При цьому стохастичні процеси тільки модифікують регулярний рух частинок, формуючи розподіл за швидкостями, подібний до гаусового. В ряде экспериментов определялось скоростное распределение пылинок, локализованных в приповерхностном слое плазмы вблизи электрода. Дисперсия скорости указывала на то, что кинетическая температура пылинок значительно превышает температуру плазменного окружения. Соответственно возник вопрос о стохастических механизмах аномального нагрева пылинок. Предложена модель, в которой кинетическая энергия пылинок обусловлена значительной потенциальной энергией, которой частицы обладают в момент высвобождения из кристаллической структуры при плавлении. При этом стохастические процессы только модифицируют регулярное движение частиц, формируя распределение по скоростям, подобное гауссовому.